RUNNING HIGH JUMP TECHNIQUE YUGURIB KELIB BALANDLIKKA SAKRASHLAR TEXNIKASI (Conferencea, 2025)
The document discusses various techniques for jumping in athletics, focusing on methods like the "Wave Technique," "Rolling Over Technique" (Perekat), and "Perekidnoy Technique." Each technique is analyzed based on the phases of the jump, such as the run-up, take-off, bar clearance, and landing. Special emphasis is placed on the technical requirements and coordination skills needed to execute these jumps effectively. The document also highlights the physical and technical training necessary to ensure proper execution and safe landings.